Human Resources in the Family Business Maximizing the Power of Your People - Schuman, Amy M.; Sage-Hayward, Wendy; Ransburg, David (A Family Business Publication, 2016)
This book will help HR managers and founders/owners develop a formal process within the company and also provide insights from family firms on how to manage sensitive topics ranging from family member compensation; family member appraisal, etc., and serves as a guide to HR managers struggling to get a "seat at the table" in family firms.